2021
DOI: 10.1007/s11864-021-00829-0
|View full text |Cite
|
Sign up to set email alerts
|

Should Loss of Appetite Be Palliated in Patients with Advanced Cancer?

Abstract: Opinion statement Loss of appetite is common among patients with advanced cancer. However, it remains controversial how, when, and if to palliate this symptom. Here, we provide an update on recent as well as past literature to address the question of whether loss of appetite should be palliated in patients with advanced cancer. In our opinion—and as discussed here—we believe that this symptom should be palliated, although perhaps not always with pharmacologic interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The most prevalent sign of NIS during chemotherapy in this study is lossing of appetite. Previous research has shown that patients with advanced malignancies are more likely to experience appetite loss [15], which is typically brought on by tumor growth, the side effects of treatment, and psychosocial stress associated with the tumor [16,17]. For instance, 10,753 individuals with advanced pancreatic cancer were investigated by Mavros et al[18].…”
Section: Discussionmentioning
confidence: 99%
“…The most prevalent sign of NIS during chemotherapy in this study is lossing of appetite. Previous research has shown that patients with advanced malignancies are more likely to experience appetite loss [15], which is typically brought on by tumor growth, the side effects of treatment, and psychosocial stress associated with the tumor [16,17]. For instance, 10,753 individuals with advanced pancreatic cancer were investigated by Mavros et al[18].…”
Section: Discussionmentioning
confidence: 99%
“…A limitation in this study is that we did not stratify the data by cancer type to explore appetite by specific cancer types, as the cohort was assessed as too small. However, loss of appetite is a major symptom in advanced cancer, where patients diagnosed with some cancer types, such as cancer in pancreas, are at a heightened risk [ 52 , 53 ]. Suggested future studies exploring loss of appetite in specific cancer types would contribute valuable knowledge to this field.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of appetite is also a prevalent symptom in advanced cancer patients [ 5 ] and has been related to worse quality of life, anxiety, and depression [ 8 –[ 9 , 11 ]– 12 ]. Ehret et al [ 33 ], in their article “Should Loss of Appetite Be Palliated in Patients with Advanced Cancer?” I concluded that the decision on the management of this symptom should be based on the expanded discussion among health professionals, patients, and family members, to assess how important appetite is for patients and their families. The management of this symptom will benefit from pharmacological drugs and nutritional and psychological follow-up [ 33 ].…”
Section: Discussionmentioning
confidence: 99%